2009
DOI: 10.1016/j.cell.2009.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI Undergoes Cargo-Mediated Dimerization

Abstract: Myosin VI is the only known molecular motor that moves toward the minus ends of actin filaments; thus, it plays unique roles in diverse cellular processes. The processive walking of myosin VI on actin filaments requires dimerization of the motor, but the protein can also function as a nonprocessive monomer. The molecular mechanism governing the monomer-dimer conversion is not clear. We report the high-resolution NMR structure of the cargo-free myosin VI cargo-binding domain (CBD) and show that it is a stable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
136
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 62 publications
9
136
0
Order By: Relevance
“…While this study was under review, a publication appeared that presented the structure of a Dab2 peptide bound to a fragment of the cargo-binding domain (CBD) of myosin VI (25). The CBD-Dab2 peptide complexes dimerized, consistent with our observations.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…While this study was under review, a publication appeared that presented the structure of a Dab2 peptide bound to a fragment of the cargo-binding domain (CBD) of myosin VI (25). The CBD-Dab2 peptide complexes dimerized, consistent with our observations.…”
Section: Discussionsupporting
confidence: 77%
“…It is also noteworthy that the short (39-aa) Dab2 peptide used in the work of Yu et al (25) has a high affinity for the myosin VI CBD (Ϸ50 nM), in contrast to our much larger tDab2 fragment. Our tDab2 contains the 39-aa peptide, but it must not be readily accessible.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The tail domain of myosin VI binds to the 39-residue fragment of the vesicle adaptor Dab2, which induces dimerization of the tail/Dab2 peptide complex (40). In the present study, it is suggested that, unlike myosin VI/ Dab2 binding, the binding of the targeting molecule, MyRip, does not directly promote dimer formation.…”
Section: Discussionmentioning
confidence: 57%
“…However, the parallel coiled-coil dimerization model has been directly demonstrated only in myosin II and V (7,8). Instead of coiled-coil-mediated dimerization, certain unconventional myosins have been shown to undergo cargo bindingmediated dimerization (9,10). It is possible that the coiled-coil region interactions and cargo binding function synergistically in modulating the dimerization of some myosins.…”
mentioning
confidence: 99%